Determinants Of Fruit And Vegetable Consumption Based On The Health Belief Model In Students Of Dharma Karya Junior High School, South Tangerang City, Banten - Keysha Adelya; Rifa Salsa Nabilla; Najwa Nurrahmah; Luqman Effendi (International Journal of Health Engineering and Technology, 2026)
Fruit and vegetable consumption among adolescents in Indonesia is still relatively low and has the potential to cause various health problems in the future. This study aims to describe the determinants of fruit and vegetable consumption based on the Health Belief Model (HBM) in junior high school students of Dharma Karya UT in South Tangerang City, Banten. The study used a descriptive method with a quantitative approach. The study sample consisted of 50 students selected using a total sampling technique. Data collection was conducted using a pre-test questionnaire that measured five HBM constructs: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy. Data analysis was conducted descriptively using frequency distributions, percentages, and average values. The results showed that the majority of respondents had good fruit and vegetable consumption behavior at 56.0%. In the HBM construct, perceived benefits had the highest percentage at 82.0%, followed by self-efficacy at 75.2%, perceived severity at 70.3%, and perceived susceptibility at 66.8%. Meanwhile, perceived barriers had the lowest percentage at 52.0%, indicating that there are still obstacles in getting used to consuming fruits and vegetables among adolescents. The conclusion of this study shows that the determinants of fruit and vegetable consumption based on the Health Belief Model in Dharma Karya UT Middle School students are generally in the quite good category, but perceived barriers are still a factor that needs attention in efforts to increase fruit and vegetable consumption among adolescents.